2020
DOI: 10.3390/ma13051025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide Modified with Organic Amine on the Aging Resistance, Rolling Loss and Wet-Skid Resistance of Solution Polymerized Styrene-Butadiene Rubber

Abstract: Graphene oxide (GO) was modified by p-phenylenediamine (PPD), aiming at improving the wet-skid resistance and reduce the rolling loss of solution polymerized styrene-butadiene rubber (SSBR). PPD with amino groups enabled GO to obtain anti-aging function. The structure of modified GO (PPD-GO) was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Raman spectroscopy. Mechanical tests showed that the mechanical properties of SSBR before and after aging were improved by ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Figure 1a confirmed the corresponding FTIR spectra of GO, SiO 2 , TGO and TGOS particles. The FTIR spectrum of GO demonstrated OH vibration, C═O vibration, C═C stretching vibration and CO stretching vibration peaks at 3408, 1727, 1626 and 1061 cm −1 , respectively 15,16 . The FTIR spectrum of TGO showed that the peak at 1038 cm −1 is the stretching vibration of CN and the peak caused by the NH bond at 3440 cm −1 may overlap with the stretching vibration of OH 17 .…”
Section: Resultsmentioning
confidence: 94%
“…Figure 1a confirmed the corresponding FTIR spectra of GO, SiO 2 , TGO and TGOS particles. The FTIR spectrum of GO demonstrated OH vibration, C═O vibration, C═C stretching vibration and CO stretching vibration peaks at 3408, 1727, 1626 and 1061 cm −1 , respectively 15,16 . The FTIR spectrum of TGO showed that the peak at 1038 cm −1 is the stretching vibration of CN and the peak caused by the NH bond at 3440 cm −1 may overlap with the stretching vibration of OH 17 .…”
Section: Resultsmentioning
confidence: 94%
“…The temperature was controlled by the Berendsen thermostat, and the pressure was controlled by the Andersen barostat [16] . The van der Waals interactions were calculated by the Lennard-Jones function with a cutoff distance of 12.5 Å and the electrostatic C [17] , respectively. The FTIR spectrum of pure XNBR (Fig.…”
Section: Molecular Simulation Detailsmentioning
confidence: 99%